1970
DOI: 10.1126/science.169.3945.611
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Basis of Hashish Activity

Abstract: A sample of hashish was extracted consecutively with petroleum ether, benzene, and methanol. When tested intravenously in monkeys only the petroleum-ether fraction was active. This material was further fractionated. The only active compound isolated was Delta(1)-tetrahydrocannabinol. Cannabinol, cannabidiol, cannabichromene, cannabigerol, and cannabicyclol when administered together with Delta(1)-tetrahydrocannabinol do not cause a change in the activity of the latter, under the experimental conditions used. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
159
0
7

Year Published

1972
1972
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(168 citation statements)
references
References 12 publications
2
159
0
7
Order By: Relevance
“…This regional profile of effects is largely in accordance with the distribution of CB1 cannabinoid receptors at which THC acts (Devane et al, 1988;Mechoulam et al, 1970;Glass et al, 1997;Herkenham et al, 1990Herkenham et al, , 1991a, and THC-induced alterations in activity in these areas have also been demonstrated in previous IEG and metabolic mapping studies performed in rodents (Bloom et al, 1997;ErdtmannVourliotis et al, 1999;Mailleux et al, 1994;Margulies and Hammer, 1991;McGregor et al, 1998;Whitlow et al, 2002). In addition, human imaging studies have consistently demonstrated marked alterations in activity in frontal brain regions following acute marijuana/THC intake or chronic marijuana use (Lundqvist et al, 2001;Mathew and Wilson, 1993;Mathew et al, 1997Mathew et al, , 2002O'Leary et al, 2000O'Leary et al, , 2002Volkow et al, 1996).…”
Section: Discussionsupporting
confidence: 57%
“…This regional profile of effects is largely in accordance with the distribution of CB1 cannabinoid receptors at which THC acts (Devane et al, 1988;Mechoulam et al, 1970;Glass et al, 1997;Herkenham et al, 1990Herkenham et al, , 1991a, and THC-induced alterations in activity in these areas have also been demonstrated in previous IEG and metabolic mapping studies performed in rodents (Bloom et al, 1997;ErdtmannVourliotis et al, 1999;Mailleux et al, 1994;Margulies and Hammer, 1991;McGregor et al, 1998;Whitlow et al, 2002). In addition, human imaging studies have consistently demonstrated marked alterations in activity in frontal brain regions following acute marijuana/THC intake or chronic marijuana use (Lundqvist et al, 2001;Mathew and Wilson, 1993;Mathew et al, 1997Mathew et al, , 2002O'Leary et al, 2000O'Leary et al, , 2002Volkow et al, 1996).…”
Section: Discussionsupporting
confidence: 57%
“…Preparations of Cannabis sativa have been used for medicinal and recreational purposes for at least 4000 years and extracts of C. sativa contain over 60 different pharmacologically active components the most prominent being D 9 -tetrahydrocannabinol (D 9 -THC) and cannabidiol (Mechoulam, 1970a;Mechoulam et al, 1970b;Howlett, 2002). Cannabinoids exert their effects by binding to specific receptors located in the membrane of the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few pharmacological studies on CBD were reported before the early 1970's, showing that CBD had no cannabis-like activity. 6 The number of publications increased in this decade and reached a first peak around 1975. In this period, a Brazilian research group led by Carlini, gave an important contribution, especially about the interactions of delta9-THC with other cannabinoids, including CBD.…”
Section: Introductionmentioning
confidence: 99%